2006
DOI: 10.1590/s0074-02762006000100013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the dot enzyme-linked immunosorbent assay in comparison with standard ELISA for the immunodiagnosis of human toxocariasis

Abstract: A dot enzyme-linked immunosorbent assay (dot-ELISA) was standardized using excretory-secretory antigens ofKey words: Toxocara canis -toxocariasis -dot enzyme-linked immunosorbent assay -ELISA Human toxocariasis is a world-wide helminthic zoonosis due to the human infection by larvae of Toxocara canis, the common ascarid of dogs, and also by the cat ascarid T. cati (Schantz & Glickman 1983, Despommier 2003. The incidence of human toxocariasis is unknown because toxocariasis is not a communicable disease in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 20 publications
1
48
0
5
Order By: Relevance
“…Because of the difficulty of detecting Toxocara larvae in biopsy tissues, the diagnosis of human toxocariasis is essentially based on immunological assays such as the ELISA test using the excretorysecretory antigens from infective Toxocara larvae (TES) to detect antiToxocara antibodies, which have good sensitivity and specificity 14,18,29 . With the development of this test, several seroepidemiological studies also have been possible 5,22,33 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the difficulty of detecting Toxocara larvae in biopsy tissues, the diagnosis of human toxocariasis is essentially based on immunological assays such as the ELISA test using the excretorysecretory antigens from infective Toxocara larvae (TES) to detect antiToxocara antibodies, which have good sensitivity and specificity 14,18,29 . With the development of this test, several seroepidemiological studies also have been possible 5,22,33 .…”
Section: Introductionmentioning
confidence: 99%
“…Anti-Toxocara IgG antibodies were detected in serum samples by ELISA-IgG test using TES antigens and each serum sample was previously absorbed with total Ascaris suum adult extract in order to avoid the crossreactions in the immunoassay 29 . All sera were tested at 1:200 dilutions and all stages of the immunoassay were performed at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of eggs with sodium hypochlorite to dissolve chitinous layer tended to mimic physiological conditions (Rajapakse et al 1992). In the present study embryonated eggs were treated with 4 % sodium hypochlorite for 2 h as it was found to be optimal for subsequent hatching whereas Watthanakulpanich et al (2008) reported an optimal timing of 3 h. However varied incubation time with different concentrations of sodium hypochlorite has been reported (Gupta 1984;Bowman et al 1987;Williamson et al 1990;Shobana 2003;Roldan et al 2006).…”
Section: Discussionmentioning
confidence: 66%
“…Many authors reported about the hatching of decorticated eggs using mechanical force Smith 1989;Crowcroft and Gillespie 1991;Roldan et al 2006;Kim et al 2008). The procedure adopted in the present study avoided the washing step of the collected larvae with the medium before keeping in cultures and also gave a better recovery of larvae when compared to earlier protocols.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation